The dose-dependent effect of caffeine supplementation on performance, reaction time and postural stability in CrossFit – a randomized placebo-controlled crossover trial - Natalia Główka; Jakub Malik; Tomasz Podgórski; Rafał Stemplewski; Janusz Maciaszek; Julia Ciążyńska; Emilia E. Zawieja; Agata Chmurzynska; Paulina M. Nowaczyk; Krzysztof Durkalec-Michalski (Journal of the International Society of Sports Nutrition, 2024)
Background Caffeine (CAF) ingestion improves performance in a broad range of exercise tasks. Nevertheless, the CAF-induced, dose-dependent effect on discipline-specific performance and cognitive functions in CrossFit/High-Intensity Functional Training (HIFT) has not been sufficiently investigated. The aim of this study was to evaluate the effect of acute supplementation of three different doses of CAF and placebo (PLA) on specific performance, reaction time (RTime), postural stability (PStab), heart rate (HR) and perceived exertion (RPE).Methods In a randomized double-blind placebo-controlled crossover design, acute pre-exercise supplementation with CAF (3, 6, or 9 mg/kg body mass (BM)) and PLA in 26 moderately trained CrossFit practitioners was examined. The study protocol involved five separate testing sessions using the Fight Gone Bad test (FGB) as the exercise performance evaluation and biochemical analyses, HR and RPE monitoring, as well as the assessment of RTime and PStab, with regard to CYP1A2 (rs762551) and ADORA2A (rs5751876) single nucleotide polymorphism (SNP).Results Supplementation of 6 mgCAF/kgBM induced clinically noticeable improvements in FGBTotal results, RTime and pre-exercise motor time. Nevertheless, there were no significant differences between any CAF doses and PLA in FGBTotal, HRmax, HRmean, RPE, pre/post-exercise RTime, PStab variables or pyruvate concentrations. Lactate concentration was higher (p < 0.05) before and after exercise in all CAF doses than in PLA. There was no effect of CYP1A2 or ADORA2A SNPs on performance.Conclusions The dose-dependent effect of CAF supplementation appears to be limited to statistically nonsignificant but clinically considered changes on specific performance, RTime, PStab, RPE or HR. However, regarding practical CAF-induced performance implications in CrossFit/HIFT, 6 mgCAF/kgBM may be supposed as the most rational supplementation strategy.